2019
DOI: 10.32861/ajams.511.150.163
|View full text |Cite
|
Sign up to set email alerts
|

Handling Critical Multicollinearity Using Parametric Approach

Abstract: In regression analysis, it is relatively necessary to have a correlation between the response and explanatory variables, but having correlations amongst explanatory variables is something undesired. This paper focuses on five methodologies for handling critical multicollinearity, they include: Partial Least Square Regression (PLSR), Ridge Regression (RR), Ordinary Least Square Regression (OLS), Least Absolute Shrinkage and Selector Operator (LASSO) Regression, and the Principal Component Analysis (PCA). Monte … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…One possibility to correct this problem is using Principal Component Regression (PCR), which is a linear regression using principal components. Maxwell et al [ 7 ] wrote an article to tackle with multicollinearity effects and here 5 methodologies were tested: Partial Least Square Regression (PLSR), Ridge Regression (RR), Ordinary Least Square Regression (OLS), Least Absolute Shrinkage and Selector Operator (LASSO) Regression, and the Principal Component Regression (PCR). To compare the 5 methodologies, they used a different number of observations and a number of predictor variables.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One possibility to correct this problem is using Principal Component Regression (PCR), which is a linear regression using principal components. Maxwell et al [ 7 ] wrote an article to tackle with multicollinearity effects and here 5 methodologies were tested: Partial Least Square Regression (PLSR), Ridge Regression (RR), Ordinary Least Square Regression (OLS), Least Absolute Shrinkage and Selector Operator (LASSO) Regression, and the Principal Component Regression (PCR). To compare the 5 methodologies, they used a different number of observations and a number of predictor variables.…”
Section: Introductionmentioning
confidence: 99%
“…Root Mean Square Error (RMSE) and AIC were used to compare the performance of each model. With this analysis the authors concluded that PCR has the lowest AMSE and AIC, which means that according to them, PCR is the most efficient in handling critical multicollinearity effects [ 7 ]. Lafi and Kaneene used Principal Component Analysis (PCA) to detect and correct multicollinearity effects in a veterinary epidemiological study.…”
Section: Introductionmentioning
confidence: 99%